PENERAPAN PENGARUH POSISI LATERAL INKLIN 300 TERHADAP PENCEGAHAN DEKUBITUS PADA PASIEN STROKE DI RUANG CEMPAKA RS PANTIWILASA CITARUM SEMARANG: THE IMPLEMENTATION OF 300 LATRAL INKLIN POSITION ON DECUBITUS PREVENTION ON STROKE PATIENTS AT THE CEMPAKA WARD RS PANTIWILASA CITARUM SEMARANG - Agus Prabowo; Ainnur Rahmanti (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2019)
Stroke is the sudden death of brain tissue caused by the lack of oxygen due to the impaired blood supply. Patients with stroke need to be given strengthen joints therapy, one of them is 300 lateral incline positions. The purpose of this case study is to analyze the position in stroke patients after the intervention of mobilization exercise every 2 hours for 6 days in Cempaka ward of RS Pantiwilasa Ciratum Semarang. The type of this research is descriptive case study approach method. The subjects of this study are two stroke patients with good functional outcomes, where the score for Modified Rankin Scale is between 0-2, willing to be respondents, never received a lateral 30? lateral incline therapy. The immobilization analysis is done descriptively and measured by Braden scale. Hence, the result of the study is the decrease of the risk shows by the changing of risk scale from 10 to 13. The recommendation of the research is the need of nurse consistency in mobilization to prevent decubitus in stroke patients.